2019
DOI: 10.1109/tevc.2018.2878221
|View full text |Cite
|
Sign up to set email alerts
|

ACO-A*: Ant Colony Optimization Plus A* for 3-D Traveling in Environments With Dense Obstacles

Abstract: Path planning is one of the most important problems in the development of autonomous underwater vehicles (AUVs). In some common AUV missions, e.g., wreckage search for rescue, an AUV is often required to traverse multiple targets in a complex environment with dense obstacles. In such case, the AUV path planning problem becomes even more challenging. In order to address the problem, this paper develops a two-layer algorithm, namely ACO-A*, by combining the ant colony optimization (ACO) with the A* search. Once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…However, the traditional ACO algorithm has some shortcomings, such as slow convergence speed and easy to fall into the local optimal solution. erefore, the ACO algorithm is often combined with other algorithms (such as A * [63] and PSO [64]) to solve the AUV path planning problem better. Che et al proposed an improved ACO algorithm based on PSO.…”
Section: Swarm Intelligence Algorithmsmentioning
confidence: 99%
“…However, the traditional ACO algorithm has some shortcomings, such as slow convergence speed and easy to fall into the local optimal solution. erefore, the ACO algorithm is often combined with other algorithms (such as A * [63] and PSO [64]) to solve the AUV path planning problem better. Che et al proposed an improved ACO algorithm based on PSO.…”
Section: Swarm Intelligence Algorithmsmentioning
confidence: 99%
“…In Table 6, additional information from previous research related to PSO is shown. Ant colony optimization (ACO) is usually studied under varying network environments, such as grid network and Voronoi diagram [107][108][109][110][111][112][113][114][115][116][117][118][119]. Few papers, likewise, researched GA with ACO and coordinate system [120].…”
Section: Refmentioning
confidence: 99%
“…L ARGE-SCALE optimization with high dimensionality and high computational cost has become more and more common in many research domains and engineering [1]- [4] in the era of big data [5]. Faced with such difficult problems, traditional population-based metaheuristic algorithms executed in serial would take hours or even days to find the optimum [6].…”
Section: Introductionmentioning
confidence: 99%